A Thermally Non-equlibirium Approch for CFD Simulation of a Pulse Tube Refrigerator - Sachindra Kumar Rout (Institute of Advanced Engineering and Science, 2014)
This paper deals with a new type of numerical computational fluid dynamic (CFD) approach of making more realistic to the porous media inside the regenerator of a pulse tube refrigerator. The available commercial software package FLUENT for solving Computational fluid dynamics (CFD) has capable of define a porous media and solve the governing equation for this region. But one problem arises is that inside the porous media region the software consider the fluid medium temperature and solid matrix medium temperature remains same in any spatial location which is impractical in real case. So to avoid this impractical situation we made attempt to make a non-thermally equilibrium medium inside the regenerator by putting a solid inside the regenerator, a size equal with solid matrix and added the source term to the fluid and solid of the regenerator by user define functions (UDF). In this analysis we used inertance tube pulse tube refrigerator (ITPTR) and helium is the working fluid.